Digital Transformation in Waqf and Hajj Fund Management: Sharia Compliance and Efficiency in 2025 - Muhammad Permadi; Atin Risnawati (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2026)
Digital transformation of Islamic financial institutions has become a major factor in making it easier to manage waqf and hajj funds, especially when it comes to following Sharia law and running things more smoothly. This study looks at how digital technologies could be used in 2025 to improve the governance, collection, distribution, and investment of waqf and hajj funds. The research shows how blockchain, artificial intelligence, and mobile fintech platforms can make things more open, easier to follow, and more accountable. It does this by looking at regulatory frameworks, case studies of institutions, and new technologies. It looks at how well these digital tools fit with Sharia principles to make sure that religious duties are met without lowering efficiency or public trust. The results show that digital transformation not only makes managing funds easier, but it also opens up more opportunities for beneficiaries and donors, lowers administrative costs, and promotes long-term economic and social growth. The study also talks about possible problems that need to be fixed to get the best results. These include cybersecurity risks, regulatory gaps, and barriers to digital literacy. The results show that the best way for waqf and hajj fund institutions to move forward is to use a hybrid model that combines traditional governance values ​​with cutting-edge technology. Digital transformation can make Islamic finance more effective at reaching both spiritual and social goals by encouraging innovation while protecting religious integrity. This makes waqf and hajj funds strong, clear, and useful financial tools in the modern world.